MEMBANGUN BUDAYA MADRASAH DENGAN PERAN IMPLEMENTASI KURIKULUM MERDEKA - Ummatul Khoiroh (Lembaga Pendidikan dan Pelatihan Sindotech, 2023)
This study aims to determine the Pancasila Student Profile as an effort to realize madrasa culture. The method is a library approach, including collecting library data, reading, taking notes and processing research materials. The results show that building madrasa culture is strongly influenced by the role of implementing the Independent Curriculum, because it contains the goal of realizing the Pancasila Student Profile. As is known, the competencies and characters in the Pancasila Student Profile are what Indonesian students must have both when studying and after entering society. It is hoped that the Indonesian nation will become intelligent individuals, with character and able to face the challenges of the times, compete globally but still adhere to the state philosophy which can create a prosperous life with dignity in accordance with the mandate of the 1945 Constitution which automatically constitutes madrasah culture.